Optimalisasi Identitas Desa melalui Place Branding: Pembuatan Logo, Video Profile, dan Site Plan Alun-Alun Desa - Alfina Damayanti; Inaya Alya Fatiha; Mufidatul Imanda A; Rizki Dwi Ananta; Muhammad Noufal A; Rahel Amanda Manullang; Mery Atika (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This Community Intervention activity aims to optimize the identity of Ujung Piring Village through place branding, which includes creating a village logo, profile video, and designing a site plan for the village square. The main problems faced by the village are the lack of a strong visual identity to optimise its potential and structured planning of village space/facilities. The methods used in the village site plan development activity were observation, interviews, and focus group discussions (FGDs). The results of the activity showed that the village logo successfully represented local values and history symbolically; the profile video was an effective medium for public communication; and the village square site plan provided direction for the development of a functional, aesthetic public space that supports social interaction. This activity proves that place branding can strengthen village identity, increase community engagement, and open up opportunities for village economic development. Further evaluation and monitoring are needed to assess the long-term impact of the implementation of this work program.